ANALISA METODE CRITICAL PATH METHOD PADA PROYEK PEMBANGUNAN ELYON CHRISTIAN SCHOOL SURABAYA - Michella Beatrix (Fakultas Teknik, Universitas Wiraraja, 2019)
In every construction project implementation there are three important things that become the main focus, cost, quality and time. The planned and well-structured project completion time will determine the success of each project. In the project completion time planning things to note are the work items that pass through the critical path, this is because the work items that pass through the critical path are very influential on the project completion time which if the work items pass through the critical path are delayed then the project completion time will also be late. This study uses the Critical Path Method in the form of a network diagram using data on the Elyon Christian School Surabaya project. The results obtained in this study are 9 work items that are in the critical path, the work code B1-C1-D1-E1-F1-G1-H1-I1-I2.